Agreement between self-reported and objectively measured smartphone use among adolescents and adults - Kimberly M. Molaib; Xiaoran Sun; Nilam Ram; Byron Reeves; Thomas N. Robinson (Computers in Human Behavior Reports)
Almost everything we think we know about the prevalence, correlates, risks, and benefits of smartphone use is based on individuals’ self-reported estimates of use. Addressing the need for research on digital recall accuracy among adolescents and parents and for specific types of app use, in this study, we compared self-reports of past-month smartphone use and continuous objective digital trace data of smartphone use provided by 41 adolescents (Mage = 15.5, SD = 1.3, age range = 13–17 years, 56% female) and 40 parents of adolescents (Mage = 45.5, SD = 6.3, 75% mothers). Intraclass correlation coefficients (ICCs) between self-reported and objective measures of total daily use were moderate for adolescents (ICC = .65) and poor for adults (ICC = .18). Consistency between self-reported and objective use of particular types of apps varied widely, with ICCs ranging from .25 (games) to .73 (social media) among adolescents and from .26 (texting and YouTube) to .79 (games) among adults. Evidence did not support a recency bias in subjective estimates. These findings, along with prior research in other samples, make a strong case that it is time to abandon the use of self-report measures of smartphone use in research on its effects.